Life-Threatening Obstructive Sleep Apnea Caused by Adenoid Hypertrophy in an Infant with Noonan Syndrome - Sonia Khirani; Nicolas Leboulanger; Adriana Ramirez; Brigitte Fauroux (Case Reports in Pediatrics)
Adenoidectomy is a commonly performed surgery in children, even though its effectiveness is still under investigation. However, in children with risk factors such as age under 3 years old, associated comorbidities, or severe obstructive sleep apneas, a high postoperative respiratory morbidity is possible. We report the case of a 15-month-old boy with Noonan syndrome and a complex clinical history, who presented with a life-threatening obstructive sleep apnea due to hypertrophy of the adenoids which resolved completely after adenoidectomy.